Effect of Supplementation of Probiotic, Prebiotic and Synbiotic on Growth Performance in Nellore Brown Lambs (Indian Journal of Animal Production and Management, 2024)
Small ruminant production provides sustainable income to small and marginal farmers under rainfed  agriculture in India. Supplementation of feed additives like probiotics and prebiotics can reduce the  usage of antibiotics in sheep production. Keeping this in view an experiment was conducted to study  the effect of probiotics (Saccharomyces cerevisiae and Lactobacillus sporengens) and Mannan  oligosaccharahides (MOS) as prebiotics and combination of both probiotic and prebiotic as synbiotic  supplementation on body weight gain in Nellore Brown lambs. Data on body weight was collected  and analysed statistically for significance. The average daily gain in different treatment groups were  recorded as 110.99±5.23g, 135.85±4.66g, 174.71±6.3g and 148.09±3.87g in Control, T1, T2 and T3  groups, respectively. Supplementation of probiotic, prebiotic and synbiotic have significant effect on  daily body weight gain in Nellore brown lambs.
Keywords: Probiotics; Prebiotics; Synbiotics; growth performance; Nellore Brown lambs